Interlinking Human-Derived Leukemia Cells with Clinicopathological Therapeutics: Exploring Capsaicin's Anti-Cancer Mechanisms/potential for Leukemia Patients: Interlinking Human-Derived Leukemia Cells with Clinicopathological Therapeutics - Mastoor, Maryam; Choudhry, Faiza; Khurshid, Aina; Naval, Ama tul; Asad, Jamal; Khaliq, Shagufta; Devi, Durga (Pakistan Journal of Health Sciences, 2024)
Capsaicin, a bioactive compound isolated from chilli peppers, comes out as a potential agent for its anti-proliferation role in leukemia patients’ therapy. Objectives: This systematic review describes the Clinicopathological therapeutic potential of capsaicin against leukemia emphasizing the mechanism by which it inhibits growth through apoptosis, the cell cycle, and regulation of oncogenic signalling pathways in human-derived leukemia cell lines. Methods: According to PRISMA guidelines, the 75 studies were obtained from the various databases January 2013 and April 2024; Semantic Scholar, Google Scholar, PubMed as well as Frontiers and Link Springer. 50% (38) of the articles were taken from Semantic Scholar, 30% (22) from Google Scholar and 20% (15) from other search engines including PubMed and Link Springer. The papers included the inclusion criteria of PRISMA based on demographics, key outcomes and Anti-Cancer mechanisms majorly. Results: Capsaicin research published in America, Europe, Asia and Africa proves that it regulates vital processes at the cellular level including production of ROS, inhibition of NF-κB, STAT3, MAPK and cellular apoptosis. As human-derived cell lines are playing a pivotal role in cancer therapy, silicon methodologies along with in-vitro and in-vivo verification also shed more light on the improvement by capsaicin of the effectiveness of standard chemotherapeutic agents in combination with preferential killing of leukemic cells. Conclusions: Significantly, there were low levels of cytotoxicity of capsaicin to normal peripheral blood hematopoietic cells indicating that the compound is safe to use inhibiting the key oncogenic pathways and enhancing the efficacy of existing chemotherapeutic agents makes it a promising candidate for future therapeutic development.